Trace Element Supplementation of Livestock in New Zealand: Meeting the Challenges of Free-Range Grazing Systems - Neville D. Grace; Scott O. Knowles (Veterinary Medicine International)
Managing the mineral nutrition of free-range grazing livestock can be challenging. On farms where grazing animals are infrequently yarded, there are limited opportunities to administer trace element supplements via feeds and concentrates. In New Zealand, where the majority of sheep, cattle, and deer graze pasture year round, inadequate intake of cobalt, copper, iodine and selenium is prevalent. Scientists and farmers have developed efficient strategies to monitor and treat these dietary deficiencies. Supplementation methods suited to grazing livestock include long-acting injections, slow-release intraruminal boluses, trace element-amended fertilisers, and reticulated water supplies on dairy farms.